THE ROLE OF HUMAN CAPITAL MANAGEMENT IN DIGITAL TRANSFORMATION AND ITS IMPACT ON THE ECONOMY - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
The role of Human Resource Management (HRM) in digital transformation is becoming increasingly important as a key driver of change in today's business environment. Digital transformation has demanded strategic adjustments that utilise technology to improve operational efficiency and create competitive advantage. The study in this research uses the literature method. The results show that First, HR management plays the role of facilitator, ensuring employees get the necessary training to deal with new technology, and supporting organisational culture change. Second, it reviewed its role in talent recruitment and retention in the digital age, using advanced technology tools to manage employee data and assist strategic decision-making. Finally, the impact of digital transformation on operational efficiency and employee productivity, leading to improved economic performance of the organisation, is discussed. Thus, the importance of effective integration between HR management and digital transformation strategies to ensure the economic success of organisations in this ever- evolving era.